2022
DOI: 10.3390/life12040580
|View full text |Cite
|
Sign up to set email alerts
|

Galvanotactic Migration of Glioblastoma and Brain Metastases Cells

Abstract: Galvanotaxis, the migration along direct current electrical fields, may contribute to the invasion of brain cancer cells in the tumor-surrounding tissue. We hypothesized that pharmacological perturbation of the epidermal growth factor (EGF) receptor and downstream phosphatidylinositol 3-kinase (PI3K)/AKT pathway prevent galvanotactic migration. In our study, patient-derived glioblastoma and brain metastases cells were exposed to direct current electrical field conditions. Velocity and direction of migration we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Although these studies observed the different responses of the glial cells and neuronal cells to the applied EF stimulation, the mechanism that controls the migration direction of the cells is not clear. A previous study showed that the glioma cell migration can be guided to move toward the anodal pole on a 2D cell culture dish [ 14 , 30 ]. Interestingly, glioma originates from glial cells, and astrocytes and glioma cells all showed anodal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies observed the different responses of the glial cells and neuronal cells to the applied EF stimulation, the mechanism that controls the migration direction of the cells is not clear. A previous study showed that the glioma cell migration can be guided to move toward the anodal pole on a 2D cell culture dish [ 14 , 30 ]. Interestingly, glioma originates from glial cells, and astrocytes and glioma cells all showed anodal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous bioelectric fields can dictate cell migration patterns, a phenomenon known as galvanotaxis or electrotaxis [112][113][114]. These fields can influence the movement and localization of stem cells within the niche or modulate their homing capabilities post-transplantation [115][116][117]. Within the niche, endogenous bioelectric gradients may serve as spatiotemporal guides for stem cell differentiation.…”
Section: Endogenous Electrical Cues: Directing Stem Cell Dynamics And...mentioning
confidence: 99%
“…To model electrotaxis in vitro, there is a growing number of researchers developing devices to generate electric fields to modulate tissue dynamics [ 288 ]. While it is well established that electric fields can drive migration of many different cell types [ 289 , 290 ], the latest data indicate that EM field stimulation at low (30–300 kHz) and extremely low (3–30 Hz) frequencies can modulate the fate and behavior of stem cells including effects on proliferation, differentiation, cell cycle progression, viability, morphology, and metabolism [ 291 ].…”
Section: Engineered Applications Of Biophysical Controlmentioning
confidence: 99%